Mathematical Model for Prediction of Biomass Ash Melting Temperature using Additives - Michal Holubcik; Jozef Jandacka (Communications - Scientific letters of the University of Zilina, 2014)
Some types of biomass ash have low ash melting temperature which can result in various problems in combustion processes. Ash slags and sinters can avoid heat transfer in heat exchangers, which can also cause corrosion of heat transfer surfaces. One of the ways of burning fuels with low ash melting temperature is to use additives. Ash melting temperature can be determined in a laboratory on the basis of standard STN ISO 540. Meltability of ash is characterized by the physical state of ash occurring during the heating process under well-defined conditions in the furnace. Experimental determination of ash melting temperature is quite expensive. In this work a prediction method of ash melting temperature is described. The mathematical model uses multiple linear regression where input parameters are the known chemical composition of fuel ash and used additive converted to an amount of SiO2, CaO, K2O, MgO and Al2O3. The mathematical model is relatively accurate with real ash melting temperatures and reaches accuracy about of 90 % compared with ash melting temperatures obtained by STN ISO 540 method in a laboratory.